Removal of Cu2+, Pb2+ , And Ni 2+ Ions From Simulated Waste Water By Ion Exchange Method On Zeolite And Purolite C105 Resin (Journal of Engineering, 2013)
The removal of heavy metal ions from wastewater by ion exchange resins ( zeolite and purolite C105), was investigated. The adsorption process, which is pH dependent, shows maximum removal of metal ions at pH 6 and 7 for zeolite and purolite C105 for initial metal ion concentrations of 50-250 mg/l, with resin dose of 0.25-3 g. The maximum ion exchange capacity was found to be 9.74, 9.23 and 9.71 mg/g for Cu2+, Pb2+, and Ni2+ on zeolite respectively, while on purolite C105 the maximum ion exchange capacity was found to be 9.64 ,8.73 and 9.39 for Cu2+, Pb2+, and Ni2+ respectively. The maximum removal was 97-98% for Cu2+ and Ni2+ and 92- 93% for Pb2+ on zeolite, while it was 93-94% for Cu2+, 96-97% for Ni2+, and 87-88% for Pb2+ on purolite C105. The obtained sorption affinity sequence was Cu 2+> Ni2+> Pb2+ in both resins. Langmuir isotherm expressions were found to give better fit to the experimental data compared to Freundlich and BET models. Kinetic data correlated well with Lagergren first order kinetic model, indicating the reversible reaction with an equilibrium being established between liquid and solid phase.